Policy Network in Tangerang Live Application - Restu Ramadhan; Ria Arifianti; Riswanda Riswanda (Universitas Sultan Ageng Tirtayasa, 2020)
Tangerang City as a city that is implementing the Smart City concept to solve city problems and improve city governance. Since 2016 the Tangerang City Government has been running Smart City by creating a Tangerang LIVE Room with the Tangerang LIVE vision of Liveable, Investable, Visitable, and E-City, the vision is based on the use of information, technology and communication to create a public service system and employee work to the community to be more optimal, efficient and effective. Innovations that are being developed by the City of Tangerang have successfully made 174 Applications. The success of the application made 31 City Governments and Agencies in Indonesia adopt applications owned by the City of Tangerang. The principle of the Tangerang Smart City Partnership aims to accelerate regional development at the local level, increase economic growth and community welfare through optimizing the use of regional resources. A qualitative approach was used in this research by collecting data through library research, interviews and documentation of informants who were directly involved in carrying out these activities. The analysis of this study uses Frans Van Waarden's theory model, the results of the study show that: (1) The actors involved have been from all walks of life, but it is better to increase their involvement, (2) The function of each actor should be improved again to achieve the Tangerang policy objectives Live (3) Network structure is already running, but the good Leading Sector is transferred to the Mayor (4) Institutionalization has not been regulated (5) Rules of action have not been regulated in mayor regulations or regional regulations specifically regarding Smart City (6) Power Relations have been running with good (7) The actor's strategy is well underway to manage his dependency.